(3cfg GdUhGH aj ShA eYGTQI GdCUMGHs
(3ChdgG (B:s
(3CeG HYO, aEf af GdQhGjGJ YfO GdGee GdZQHjI gh af TgjQ ef afhf GdCOH, hdcf djS dg CgejI YfO GdeDdajf ef CHfGA GdYQH s
(3BNQgG (B:s
(3hHYOg JCSa Ydi haGI HQgGf CafOj ZGjI GdCSa, abdfG dg(B: (3Ef s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B158 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs